PENGARUH LKPDLBERBASIS INKUIRILTERBIMBING TERHADAPLKEMAMPUAN BERPIKIRLKRITIS PESERTALDIDIK SEKOLAH DASAR - Siti Nurjanah; Muhammad Arya Wirayuda, Deviyanti Pangestu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
he problemgof thisrresearch wasfthe low critical thinkingwability in the learning of science in grade V elementary school studentslbecause teachers haven’t maximized theluse of teaching materials. Thelpurpose oflthis studylwas toldetermine theleffect of worksheet basedlon guided inquiry on the criticallthinking ability of science inlgrade V elementary schoolrstudents. The research methodhwas a quasi-experimentalimethod with aione-group pretest-posttestidesign.lThelresearch sample consisted of 21rclass students. Data collection techniquesdused test techniques. The results showed that therelwas alsignificant effect on the use of worksheetvbased on guided inquiry on the criticallthinking ability of science in grade 5 students of SD Negerii 4 Metroi Utara.